Determinants of PBB P-2 Compliance Level in Kendit Village, Kendit District, Situbondo District - Nur Holifah; Diyah Probowulan; Achmad Syahfrudin Zulkarnnaeni (West Science Business and Management, 2024)
Tax literacy is the ability to understand and access tax regulations, this means dealing with taxpayers who have knowledge, awareness and tax compliance. Compliance with the payment of Land and Building Tax in Kendit Village, Kendit District, Situbondo Regency, in this village there is still a lack of public awareness regarding PBB payments. This is proven by the need to be reminded of awareness regarding the time for PBB payments by the village which is enforced by the hamlet head of each hamlet, but when reminded they immediately pay. The first aim of this research is to find out the factors that influence the level of tax compliance literacy on taxpayer compliance. Earth and Buildings. Second, to find out the factors that influence Land and Building Taxpayers. The methodology used in this research is Tax Compliance theory. Tax complaints can be identified from tax compliance in registration, tax compliance in returning notification letters, tax compliance in calculating and paying unpaid taxes and tax compliance in settling arrears. So a Tax Complaint is when a taxpayer fulfills his or her tax obligations and rights. By using hypothesis testing with a significant value of 0.04 to test the findings, it is established that the degree of education affects the factors that determine the literacy level of Land and Building Tax compliance. This study's hypothesis testing with a significant value of 0.45 demonstrates how socioeconomic status affects the factors that determine the literacy level of Land and Building Tax compliance. Hypothesis testing with a significant value of 0.001 in this study demonstrates that taxpayer compliance impacts the factors that determine the literacy level of Land and Building Tax compliance. Through hypothesis testing, this study demonstrates that tax fines have an impact on the factors that determine the literacy level of Land and Building Tax compliance, with a significant value of 0.023. The study's conclusion, which is based on the data examining the effects of socioeconomic status, education level, taxpayer compliance, and tax sanctions on the compliance literacy of P2 Land and Building Taxpayers in Kendit Village, Kendit District, Situbondo Regency, demonstrates that compliance literacy levels rise in direct proportion to socioeconomic status, education level, taxpayer compliance, and tax sanctions.